2004
DOI: 10.1128/jb.186.6.1591-1597.2004
|View full text |Cite
|
Sign up to set email alerts
|

H Protein of Bacteriophage 16-3 and RkpM Protein of Sinorhizobium meliloti 41 Are Involved in Phage Adsorption

Abstract: The strain-specific capsular polysaccharide KR5 antigen of Sinorhizobium meliloti 41 is required both for invasion of the symbiotic nodule and for the adsorption of bacteriophage 16-3. In order to know more about the genes involved in these events, bacterial mutants carrying an altered phage receptor were identified by using host range phage mutants. A representative mutation was localized in the rkpM gene by complementation and DNA sequence analysis. A host range phage mutant isolated on these phage-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
(51 reference statements)
2
15
0
Order By: Relevance
“…Phage strains 16-3⌬NC (9) and 16-3cti3 (24) were used as back-ground strains for the isolation of host range and insertional mutants, respectively. Host range mutant h109 was isolated earlier on strain GH4180 (32). New host range mutants described in this study were isolated on different bacterial mutants by the same procedure: h182 was isolated on strain AT313 (AK631 rkpZ::Tn5) (20), while h842 and h843 were isolated on strain PP4073 (25).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phage strains 16-3⌬NC (9) and 16-3cti3 (24) were used as back-ground strains for the isolation of host range and insertional mutants, respectively. Host range mutant h109 was isolated earlier on strain GH4180 (32). New host range mutants described in this study were isolated on different bacterial mutants by the same procedure: h182 was isolated on strain AT313 (AK631 rkpZ::Tn5) (20), while h842 and h843 were isolated on strain PP4073 (25).…”
Section: Methodsmentioning
confidence: 99%
“…In order to elucidate the molecular mechanism of phage 16-3 and S. meliloti 41 recognition, bacterial mutants carrying an altered phage receptor and host range phage mutants able to overcome the adsorption block have been characterized previously (32). It was shown that the RkpM protein, together with other yet uncharacterized elements, is a component of the phage receptor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genes, proteins, and chromosomal sites for several functions of the temperate phage 16-3 of Rhizobium meliloti 41 have been studied in detail (1,2,5,8,9,11,19,22,24,25). The most thoroughly analyzed region of the 16-3 genome has been the immC regulatory region which encodes a lambda type CI repressor (16-3 C repressor protein), and the cognate c cistron is flanked by two operator regions, O L and O R (3,4,6,(16)(17)(18)20).…”
mentioning
confidence: 99%
“…Genes, proteins, and chromosomal sites for several functions of the phage have been studied in more detail. These include (i) the main repressor protein, C, required for establishing and maintaining lysogeny, and the operator regions where the C protein binds (8,10,25); (ii) the components of the sitespecific recombination system (5,12,23,29,30); (iii) the immX regulatory region conferring immunity against homoimmune phages (7); and (iv) the recently identified h gene encoding the tail fiber protein (26).…”
mentioning
confidence: 99%